IL-34 Induces the Differentiation of Human Monocytes into Immunosuppressive Macrophages. Antagonistic Effects of GM-CSF and IFNγ - Foucher, Etienne D. (Public Library of Science, 2013)
IL-34 is a recently identified cytokine that signals via the M-CSF receptor and promotes monocyte survival. Depending on the environment, monocytes can differentiate into macrophages (Mφ) or dendritic cells (DC). A wide spectrum of Mφ and DC subsets, with distinct phenotypes and functions, has been described. To date, the phenotype of monocytes exposed to IL-34 remains unexplored. We report here that IL-34 induces the differentiation of monocytes into CD14(high) CD163(high) CD1a(−) Mφ (IL-34-Mφ). Upon LPS stimulation, IL-34-Mφ exhibit an IL-10(high) IL-12(low) M2 profile and express low levels of the costimulatory molecules CD80 and CD86. IL-34-Mφ exhibit poor T cell costimulatory properties, and have potent immunosuppressive properties (decrease of TCR-stimulated T cell proliferation). For all the parameters analyzed, IL-34-Mφ are phenotypically and functionally similar to M-CSF-Mφ. IL-34 appears as efficient as M-CSF in inducing the generation of immunosuppressive Mφ. Moreover, the generation of IL-34-Mφ is mediated through the M-CSF receptor, is independent of endogenous M-CSF consumption and is potentiated by IL-6. In an attempt to identify strategies to prevent a deleterious M2 cell accumulation in some pathological situations, we observed that IFNγ and GM-CSF prevent the generation of immunosuppressive Mφ induced by IL-34. IFNγ also switches established IL-34-Mφ into immunostimulatory Mφ. In conclusion, we demonstrate that IL-34 drives the differentiation of monocytes into immunosuppressive M2, in a manner similar to M-CSF, and that IFNγ and GM-CSF prevent this effect.